A kind of uranium recovery uranium absorbing auxiliary material and recovery method for uranium-containing wastewater
By adsorbing and recycling of uranyl ions in low-concentration uranyl wastewater with magnetic metal nanomaterial composite auxiliary materials, the problem of uranium mine treatment in the existing technology is solved, and efficient and safe uranium resource recycling and environmental protection are achieved.
Patent Information
- Application Number
- CN202410523334.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-04-28
- Publication Date
- 2025-01-17
- Estimated Expiration
- 2044-04-28
AI Technical Summary
The prior art is difficult to effectively treat low-concentration uranium-containing wastewater, especially because ion exchange resins are prone to poisoning and difficult to achieve resource recycling, which has led to the threat of the ecological environment of uranium mines.
Uranium absorbing auxiliary materials composed of magnetic metal nanosheets, magnetic metal nanospheres, polyvinyl alcohol and epoxy resin are used to form uranium absorbing auxiliary materials with high recycling efficiency and recycling through the composite of magnetic metal nanosheets and magnetic metal nanospheres. , the mesoporous and ester-based groups are used to adsorb uranyl ions, and the effective recovery of uranium is achieved through temperature and pH regulation.
It achieves an efficient uranium recovery rate, reduces the investment and cost of auxiliary materials, reduces the generation of toxic substances, and can be recycled, improving processing efficiency and safety.
Smart Images

Figure CN118491484B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of uranium recovery process, and in particular relates to a uranium-absorbing auxiliary material for recovering uranium from uranium-containing wastewater and a recovery method. Background Art
[0002] Nuclear power has become the main energy supply strategy that countries are currently prioritizing due to its clean, efficient and low-carbon nature. The vigorous development, promotion and use of nuclear power will inevitably increase the demand for its main fuel, natural uranium. At present, natural uranium mainly comes from terrestrial mineral uranium resources. The mining and beneficiation of terrestrial mineral uranium resources produce a large amount of uranium-containing wastewater, which seriously threatens the health of residents in the uranium mine area and the sustainable development of the ecological environment. The uranium-containing wastewater generated by the mining of terrestrial mineral uranium resources mainly comes from mine water and tailings pond heap leaching water, with a comprehensive uranium concentration of 0.5 to 3.0 mg / L, which belongs to the category of low-concentration uranium-containing wastewater. The radioactive uranium in low-concentration uranium-containing wastewater is easy to migrate and form complex pollution. In addition, the uranium concentration is low and there are many types of associated metals. The treatment of this wastewater has become one of the key and difficult issues in the protection of the ecological environment of uranium mines.
[0003] The uranium in uranium-containing wastewater exists in the form of uranyl ions complexed with coexisting anions. In actual uranium mine wastewater treatment, weakly alkaline anion exchange resins are mostly used to capture and fix uranyl ions and anion complexes. Although this method has the characteristics of high uranium retention efficiency and strong selectivity, it has problems such as easy poisoning of ion exchange resins. In addition, this treatment method makes it difficult to achieve resource recovery of waste uranium resources. Summary of the invention
[0004] The purpose of the present invention is to provide a uranium absorbing auxiliary material and a recovery method thereof. The uranium absorbing auxiliary material utilizes magnetic metal nanomaterials and adds functions on the basis of conventional magnetic metal nanomaterials to form a uranium absorbing auxiliary material that is easy to use, has high recovery efficiency and can be recycled. The recovery method is easy to operate, saves auxiliary material input, and saves costs.
[0005] To achieve the above-mentioned object, the present invention provides the following technical scheme: an auxiliary material for uranium recovery and uranium absorption in uranium-containing wastewater, the auxiliary material is composed of a mixture of magnetic metal nanosheets, magnetic metal nanospheres, polyvinyl alcohol and epoxy resin, the magnetic metal nanosheets and the magnetic metal nanospheres are composed in a mass ratio of 1:3-5, the polyvinyl alcohol is complexed on the magnetic metal nanosheets, the magnetic metal nanospheres contain a plurality of mesopores in a microscopic state, and the mesopore diameter is between 20-35 nanometers, and the epoxy resin is used to encapsulate the magnetic metal nanospheres.
[0006] The present invention adopts magnetic metal nanosheets and magnetic metal nanospheres to recover uranium wastewater, recovers uranyl ions therein, and further composites the magnetic metal nanosheets and magnetic metal nanospheres to prepare a uranium washing auxiliary material which is convenient and directly usable.
[0007] As a preferred embodiment of the present invention, the magnetic metal nanosheets are specifically one of manganese ferrite nanosheets or nickel ferrite nanosheets, and the magnetic metal nanospheres are specifically one of manganese ferrite nanospheres or nickel ferrite nanospheres.
[0008] As a preferred embodiment of the present invention, the mass ratio of the magnetic metal nanosheets to the polyvinyl alcohol is 2-3:1, and the mass ratio of the magnetic metal nanospheres to the epoxy resin is 1:3-5.
[0009] As a preferred embodiment of the present invention, the magnetic metal nanosheets are prepared by a coprecipitation method, and the specific steps include:
[0010] An ethylene glycol solution was placed inside a beaker, and then ferric chloride hexahydrate and a catalyst in a molar ratio of 1:2 were weighed and added to the beaker containing the aforementioned ethylene glycol solution. The solution was stirred under vigorous magnetic stirring for 30 minutes to form a uniform mixture, and then 1.5 g of hexamethylenetetramine was added to the mixed solution, and stirring was continued for 60 minutes. After complete dissolution, the formed uniform mixture solution was sealed in a 100 ml polytetrafluoroethylene-lined stainless steel autoclave, and then heated at 200°C for 12 hours. After the autoclave was cooled to room temperature, the resulting precursor was collected by centrifugation, washed several times with alcohol, and dried in a vacuum oven at 60°C for 24 hours. Subsequently, the sample was calcined at 450°C in a nitrogen atmosphere for 5 hours to obtain magnetic metal nanosheets.
[0011] As a preferred embodiment of the present invention, the magnetic metal nanospheres are prepared by a coprecipitation method, and the specific steps include:
[0012] Ferric chloride hexahydrate and a catalyst in a molar ratio of 1:2 were weighed separately and added to an ethylene glycol solution to dissolve. The solution was stirred under vigorous magnetic stirring for 30 minutes to form a uniform mixture. Then, 6.8 g of PVP was added to the mixed solution and stirring was continued for 1.5 hours. After complete dissolution, 7.2 g of urea was added and heated and stirred. After stirring for 30 minutes, the formed uniform mixture solution was sealed in a 100 ml polytetrafluoroethylene-lined stainless steel autoclave and then heated at 200°C for 12 hours. After the autoclave was cooled to room temperature, the obtained precursor was collected by centrifugation, washed several times with alcohol, and dried in a vacuum oven at 60°C for 24 hours. Subsequently, the sample was calcined at 450°C in a nitrogen atmosphere for 5 hours to obtain magnetic metal nanospheres with mesopores.
[0013] The added urea can be hydrolyzed to generate ammonia and carbon dioxide in the alkaline environment formed by the mixed solution at 160°C. Due to the filling of carbon dioxide, the prepared magnetic metal nanospheres can have a number of mesopores.
[0014] As a preferred embodiment of the present invention, the specific mixing steps of the auxiliary materials are as follows:
[0015] Weighing magnetic metal nanosheets and magnetic metal nanospheres in a ratio of 1:3-5 by mass, and weighing corresponding amounts of polyvinyl alcohol and epoxy resin;
[0016] ① At a temperature below 30°C, continuously introduce carbon dioxide gas into the magnetic metal nanospheres for 30-45 minutes, and keep the magnetic metal nanospheres uniformly stirred while maintaining ventilation;
[0017] ② After ventilation is completed, keep the temperature of the magnetic metal nanospheres at 35°C-55°C, add epoxy resin, stir evenly, and naturally cool to room temperature to form a solid mixture of epoxy resin and magnetic metal nanospheres;
[0018] ③ Take the magnetic metal nanosheets and polyvinyl alcohol prepared in step ①, mix them, add PVP simultaneously, stir until they are in a black suspension state, and cover the mixture obtained in step ② on the magnetic metal nanosheets to obtain a layered mixture;
[0019] ④ Dry and collect the mixture obtained in step ③ to obtain a uranium absorbing auxiliary material.
[0020] By adopting the above technical scheme, the uranium absorption auxiliary material contains magnetic metal nanosheets, wherein polyvinyl alcohol is complexed on the magnetic metal nanosheets, and then under the action of the complexing agent PVP, a number of ester groups are complexed on the magnetic metal nanosheets, and the magnetic metal nanosheets are mixed with magnetic metal nanospheres for use, and carbon dioxide gas is filled in the mesopores of the magnetic metal nanospheres, and the carbon dioxide gas is encapsulated by epoxy resin. Due to the existence of the mesopores, after the carbon dioxide gas is continuously introduced, the carbon dioxide gas can be filled in the mesopores, and the epoxy resin is solid at low temperature and can be encapsulated on the outside of the magnetic metal nanospheres, so as to seal the mesopores, so that the magnetic metal nanospheres contain carbon dioxide gas.
[0021] The present invention also provides a method for recovering uranium from uranium-containing wastewater, which uses the above-mentioned uranium absorbing auxiliary material and specifically comprises the following steps:
[0022] ① placing the prepared uranium absorbing auxiliary material into uranium-containing wastewater;
[0023] ② Heat the wastewater at a temperature of 140-160°C and keep it still for 2-3 hours;
[0024] ③ After standing, the magnetic metal nanosheets and magnetic metal nanospheres are collected by magnetic absorption to obtain liquid and solid after solid-liquid separation, and the solid is a mixture of magnetic metal nanosheets and magnetic metal nanospheres;
[0025] ④ Rinse the solid mixture with deionized water, collect the rinsed liquid after rinsing 5-6 times, mix the liquid with the liquid in step ③, collect, and cool naturally to obtain the epoxy resin in the lower layer and the clean water after uranium is separated from the upper layer;
[0026] ⑤ Place the washed solid mixture in a weak alkaline solution for washing, and recover the lower layer of solids and the upper layer of clear liquid;
[0027] ⑥ The lower layer of solid obtains magnetic metal nanosheets and magnetic metal nanospheres, which can be recycled, and the upper layer of clear liquid obtains uranium salt solution, thereby completing the recovery.
[0028] The above method is combined with the above uranium absorption auxiliary material. Since the above method is based on a temperature environment of 140-160°C, after the above uranium absorption auxiliary material is mixed with wastewater, at this temperature, the epoxy resin on the magnetic metal nanospheres melts, and the internal carbon dioxide gas enters the wastewater to adjust the pH value of the wastewater to be acidic. In the acidic environment, the magnetic nanosheets are used as carriers, and the ester groups on the magnetic nanosheets are hydrolyzed into carboxyl groups. Since the uranyl ions in the wastewater are cations, they are adsorbed with the carboxyl groups to form acidic uranyl groups attached to the magnetic metal nanosheets. Then, the uranyl ions in the wastewater can be separated by collecting the magnetic metal nanosheets and the magnetic metal nanospheres. Further, through alkaline washing, the uranyl ions can be combined with the carboxyl groups thereon to obtain uranium salt compounds, and then the collection is completed.
[0029] The invention has the beneficial effects as follows: the invention provides a uranium absorption auxiliary material, firstly, mesoporous manganese ferrite nanospheres are used as carriers, during recycling, carbon dioxide gas is carried by the manganese ferrite nanospheres, the pH value of wastewater is adjusted to make it in an acidic environment, and then the layered nature of manganese ferrite nanosheets is utilized to fully expand in the uranium wastewater, and at the same time, the layered manganese ferrite nanosheets are used as carriers to reduce the sedimentation rate of the manganese ferrite nanosheets in the wastewater, and further composite modification is performed on the manganese ferrite nanosheets, and ester groups are complexed thereon, so that uranyl ions in the wastewater can be fully absorbed, thereby achieving a high recovery rate, and the technical effect that the uranium absorption auxiliary material can be recycled is achieved, which is beneficial to reducing costs and reducing the generation of toxic substances in the recovery process. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 This is a scanning electron microscope image of the manganese ferrite nanosheet provided by the present invention;
[0031] Figure 2 This is a transmission electron microscope image of the manganese ferrite nanosphere provided by the present invention. DETAILED DESCRIPTION
[0032] In order to further understand the content, features and effects of the present invention, the following embodiments are given as examples and described in detail with reference to the accompanying drawings.
[0033] Please also refer to Figure 1 to Figure 2The following will describe in detail the auxiliary materials and recovery method for uranium recovery from uranium-containing wastewater according to the embodiment of the present invention in conjunction with the accompanying drawings. The bracket can be used in conjunction with the lifting structure.
[0034] The auxiliary material for uranium recovery and absorption in uranium-containing wastewater is composed of a mixture of magnetic metal nanosheets, magnetic metal nanospheres, polyvinyl alcohol and epoxy resin. The magnetic metal nanosheets and the magnetic metal nanospheres are composed in a mass ratio of 1:3-5. The polyvinyl alcohol is complexed on the magnetic metal nanosheets. The magnetic metal nanospheres contain a plurality of mesopores in a microscopic state, and the mesopore diameter is between 20-35 nanometers. The epoxy resin is used to encapsulate the magnetic metal nanospheres.
[0035] The magnetic metal nanosheets are specifically one of manganese ferrite nanosheets or nickel ferrite nanosheets, and the magnetic metal nanospheres are specifically one of manganese ferrite nanospheres or nickel ferrite nanospheres.
[0036] The mass ratio of the magnetic metal nanosheets to the polyvinyl alcohol is 2-3:1, and the mass ratio of the magnetic metal nanospheres to the epoxy resin is 1:3-5.
[0037] In this embodiment, magnetic metal nanosheets and magnetic metal nanospheres are selected in a mass ratio of 1:3, and manganese acetate is used as a catalyst to prepare manganese ferrite nanospheres and manganese ferrite nanosheets.
[0038] The added ethylene glycol, PVP, urea, manganese acetate and hexamethylenetetramine are all experimental-grade chemicals that are directly purchased.
[0039] First, a magnetic metal nanosheet is prepared. The magnetic metal nanosheet is prepared by a coprecipitation method, and the specific steps include:
[0040] An ethylene glycol solution was placed inside a beaker, and then ferric chloride hexahydrate and manganese acetate in a molar ratio of 1:2 were weighed and added to the beaker containing the aforementioned ethylene glycol solution. The solution was stirred under vigorous magnetic stirring for 30 minutes to form a uniform mixture, and then 1.5 g of hexamethylenetetramine was added to the mixed solution, and stirring was continued for 60 minutes. After complete dissolution, the formed uniform mixture solution was sealed in a 100 ml polytetrafluoroethylene-lined stainless steel autoclave, and then heated at 200°C for 12 hours. After the autoclave was cooled to room temperature, the resulting precursor was collected by centrifugation, washed with alcohol several times, and dried in a vacuum oven at 60°C for 24 hours. Subsequently, the sample was calcined at 450°C in a nitrogen atmosphere for 5 hours to obtain manganese ferrite nanosheets, such as Figure 1 shown.
[0041] Secondly, the magnetic metal nanospheres are prepared by co-precipitation method, and the specific steps include:
[0042] Ferric chloride hexahydrate and manganese acetate in a molar ratio of 1:2 were weighed and added to an ethylene glycol solution to dissolve. The solution was stirred under vigorous magnetic stirring for 30 minutes to form a uniform mixture. Then, 6.8 g of PVP was added to the mixed solution and stirred for 1.5 hours. After complete dissolution, 7.2 g of urea was added and heated and stirred. After stirring for 30 minutes, the formed uniform mixture solution was sealed in a 100 ml polytetrafluoroethylene-lined stainless steel autoclave and then heated at 200°C for 12 hours. After the autoclave was cooled to room temperature, the obtained precursor was collected by centrifugation, washed with alcohol several times, and dried in a vacuum oven at 60°C for 24 hours. Subsequently, the sample was calcined at 450°C in a nitrogen atmosphere for 5 hours to obtain manganese ferrite nanospheres with mesopores, such as Figure 2 shown.
[0043] The auxiliary materials are prepared by using the manganese ferrite nanosheets and manganese ferrite nanospheres prepared above, and the specific mixing steps are as follows:
[0044] Weighing magnetic metal nanosheets and magnetic metal nanospheres in a 1:3 mass ratio, and weighing polyvinyl alcohol in a 1:2 mass ratio of the magnetic metal nanosheets and epoxy resin in a 1:3 mass ratio of the magnetic metal nanospheres;
[0045] ① At a temperature below 30°C, continuously introduce carbon dioxide gas into the magnetic metal nanospheres for 30-45 minutes, and keep the magnetic metal nanospheres uniformly stirred while maintaining ventilation;
[0046] ② After ventilation is completed, keep the temperature of the magnetic metal nanospheres at 35°C-55°C, add epoxy resin, stir evenly, and naturally cool to room temperature to form a solid mixture of epoxy resin and magnetic metal nanospheres;
[0047] ③ Take the magnetic metal nanosheets and polyvinyl alcohol prepared in step ①, mix them, add PVP simultaneously, stir until they are in a black suspension state, and cover the mixture obtained in step ② on the magnetic metal nanosheets to obtain a layered mixture;
[0048] ④ Dry and collect the mixture obtained in step ③ to obtain a uranium absorbing auxiliary material.
[0049] The uranium absorbing auxiliary material prepared above is used to recover uranium wastewater, which specifically includes the following steps:
[0050] ① placing the prepared uranium absorbing auxiliary material into uranium-containing wastewater;
[0051] ② Heat the wastewater at a temperature of 140-160°C and keep it still for 2-3 hours;
[0052] ③ After standing, the magnetic metal nanosheets and magnetic metal nanospheres are collected by magnetic absorption to obtain liquid and solid after solid-liquid separation, and the solid is a mixture of magnetic metal nanosheets and magnetic metal nanospheres;
[0053] ④ Rinse the solid mixture with deionized water, collect the rinsed liquid after rinsing 5-6 times, mix the liquid with the liquid in step ③, collect, and cool naturally to obtain the epoxy resin in the lower layer and the clean water after uranium is separated from the upper layer;
[0054] ⑤ Place the washed solid mixture in a weak alkaline solution for washing, and recover the lower layer of solids and the upper layer of clear liquid;
[0055] ⑥ The lower layer of solid obtains magnetic metal nanosheets and magnetic metal nanospheres, which can be recycled, and the upper layer of clear liquid obtains uranium salt solution, thereby completing the recovery.
[0056] In this embodiment, manganese ferrite nanospheres with mesopores are first used as carriers. During recycling, carbon dioxide gas is carried by the manganese ferrite nanospheres to adjust the pH of the wastewater so that it is in an acidic environment. The layered nature of the manganese ferrite nanosheets is then utilized to fully expand in the uranium wastewater. At the same time, the layered manganese ferrite nanosheets as carriers can reduce their sedimentation rate in the wastewater. They are further subjected to composite modification and chelated with ester groups thereon, which can fully adsorb uranyl ions in the wastewater, thereby achieving a high recovery rate. The technical effect of the uranium adsorption auxiliary material being recyclable is beneficial to reducing costs and reducing the generation of toxic substances during the recovery process.
[0057] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A uranium recovery and uranium absorption auxiliary material for uranium-containing wastewater, characterized in that: The auxiliary material is composed of a mixture of magnetic metal nanosheets, magnetic metal nanospheres, polyvinyl alcohol and epoxy resin, wherein the magnetic metal nanosheets and the magnetic metal nanospheres are composed in a mass ratio of 1:3-5, the polyvinyl alcohol is complexed on the magnetic metal nanosheets, the magnetic metal nanospheres contain a plurality of mesopores in a microscopic state, and the mesopore diameter is between 20-35 nanometers, the epoxy resin is used to encapsulate the magnetic metal nanospheres, the magnetic metal nanosheets are specifically one of manganese ferrite nanosheets or nickel ferrite nanosheets, the magnetic metal nanospheres are specifically one of manganese ferrite nanospheres or nickel ferrite nanospheres, and the auxiliary material specific mixing steps are as follows: Weigh the magnetic metal nanosheets and magnetic metal nanospheres in a ratio of 1:3-5 by mass, and weigh the polyvinyl alcohol and epoxy resin in corresponding mass portions; ① At a temperature below 30°C, continuously introduce carbon dioxide gas into the magnetic metal nanospheres for 30-45 minutes, and keep the magnetic metal nanospheres uniformly stirred while maintaining ventilation; ② After ventilation is completed, keep the temperature of the magnetic metal nanospheres at 35℃-55℃, add epoxy resin, stir evenly, and naturally cool to room temperature to form a solid mixture of epoxy resin and magnetic metal nanospheres; ③ Take the magnetic metal nanosheets and polyvinyl alcohol prepared in step ①, mix them, add PVP simultaneously, stir until a black suspension is formed, and cover the mixture obtained in step ② on the magnetic metal nanosheets to obtain a layered mixture; ④ Dry and collect the mixture obtained in step ③ to obtain a uranium absorbing auxiliary material.
2. The auxiliary material for uranium recovery and absorption of uranium from uranium-containing wastewater according to claim 1, characterized in that: The mass ratio of the polyvinyl alcohol to the magnetic metal nanosheets is 1:2-3.
3. The auxiliary material for uranium recovery and absorption of uranium from uranium-containing wastewater according to claim 1, characterized in that: The mass ratio of the magnetic metal nanospheres to the epoxy resin is 1:3-5.
4. The auxiliary material for uranium recovery and absorption of uranium from uranium-containing wastewater according to claim 1, characterized in that: The magnetic metal nanosheets are prepared by a coprecipitation method, and the specific steps include: Place ethylene glycol solution in a beaker, weigh ferric chloride hexahydrate and a catalyst in a molar ratio of 1:2 and add them to the beaker containing the ethylene glycol solution. Stir the solution vigorously under magnetic stirring. 30 min to form a uniform mixture, and then 1.5 g of hexamethylenetetramine was added to the mixed solution and stirred for 60 min. After complete dissolution, the formed uniform mixture solution was sealed in a 100 ml polytetrafluoroethylene-lined stainless steel autoclave and then heated at 200 °C for 12 h. After the autoclave was cooled to room temperature, the resulting precursor was collected by centrifugation, washed with alcohol several times, and dried in a vacuum oven at 60 °C for 24 h. Subsequently, the sample was calcined at 450 °C in a nitrogen atmosphere for 5 h to obtain magnetic metal nanosheets.
5. The auxiliary material for uranium recovery and absorption of uranium from uranium-containing wastewater according to claim 1, characterized in that: The magnetic metal nanospheres are prepared by a coprecipitation method, and the specific steps include: Ferric chloride hexahydrate and a catalyst in a molar ratio of 1:2 were weighed separately and added to an ethylene glycol solution to dissolve. The solution was stirred under vigorous magnetic stirring for 30 minutes to form a uniform mixture. Then 6.8 g of PVP was added to the mixed solution and stirring was continued for 1.5 hours. After complete dissolution, 7.2 g of urea was added and heated with stirring. After stirring for 30 minutes, the formed uniform mixture solution was sealed in a 100 ml polytetrafluoroethylene-lined stainless steel autoclave and then heated at 200°C for 12 hours. After the autoclave was cooled to room temperature, the resulting precursor was collected by centrifugation, washed several times with alcohol, and dried in a vacuum oven at 60°C for 24 hours. Subsequently, the sample was calcined at 450°C in a nitrogen atmosphere for 5 hours to obtain magnetic metal nanospheres with mesopores.
6. A method for recovering uranium from uranium-containing wastewater, using the uranium absorbing auxiliary material of claims 1-5, characterized in that: The specific steps include: ① placing the prepared uranium absorbing auxiliary material into uranium-containing wastewater; ② Heat the wastewater at a temperature of 140-160°C and keep it still for 2-3 hours; ③ After standing, the magnetic metal nanosheets and magnetic metal nanospheres are collected by magnetic absorption to obtain liquid and solid after solid-liquid separation, and the solid is a mixture of magnetic metal nanosheets and magnetic metal nanospheres; ④ Rinse the solid mixture with deionized water, collect the rinsed liquid after rinsing 5-6 times, mix the liquid with the liquid in step ③, collect, and cool naturally to obtain epoxy resin in the lower layer and clean water after uranium is separated from the upper layer; ⑤ Place the washed solid mixture in a weak alkaline solution for cleaning, and recover the lower layer solids and the upper layer solids. Clear liquid; ⑥ The lower layer of solid obtains magnetic metal nanosheets and magnetic metal nanospheres, which can be recycled, and the upper layer of clear liquid obtains uranium salt solution, thereby completing the recovery.
Citation Information
Patent Citations
Ferroferric oxide porous ball having micro-nano structure, and preparation method of ferroferric oxide porous ball
CN102153151A
Fe3O4 nanometer catalyst for Fischer-Tropsch synthesis and preparation method of Fe3O4 nanometer catalyst
CN105032422A